2007
DOI: 10.1182/blood.v110.11.2572.2572
|View full text |Cite
|
Sign up to set email alerts
|

Initial Results from an International Study in Relapsed/Refractory Aggressive Non-Hodgkin’s Lymphoma To Confirm the Activity, Safety and Criteria for Predicting Response to Lenalidomide Monotherapy.

Abstract: Background: Lenalidomide (Revlimid®) has demonstrated activity with manageable side effects in relapsed/refractory aggressive non-Hodgkin’s lymphoma (NHL). In the initial pilot study, response to lenalidomide was associated with low tumor burden, long duration from prior rituximab and high absolute lymphocyte count. Aims: To confirm the activity and safety of lenalidomide monotherapy in patients with relapsed/refractory aggressive NHL in an international setting and Determine whet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2008
2008
2009
2009

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…In two studies published in abstract form using the immuno-modulator Revlimid to treat relapsed/refractory aggressive NHL showed that patients with higher ALC at the time of Revlimid therapy experienced better response to treatment. In one study [13], patients with an ALC > 0.6 3 10 9 /L had a 33% response to Revlimid when compared with 0% response to those who did not. Similarly, in the other study [14], patients with an ALC > 0.6 3 10 9 /L had a 42% response to Revlimid when compared with only 9% response to patients with an ALC 0.6 3 10 9 /L.…”
Section: Discussionmentioning
confidence: 98%
“…In two studies published in abstract form using the immuno-modulator Revlimid to treat relapsed/refractory aggressive NHL showed that patients with higher ALC at the time of Revlimid therapy experienced better response to treatment. In one study [13], patients with an ALC > 0.6 3 10 9 /L had a 33% response to Revlimid when compared with 0% response to those who did not. Similarly, in the other study [14], patients with an ALC > 0.6 3 10 9 /L had a 42% response to Revlimid when compared with only 9% response to patients with an ALC 0.6 3 10 9 /L.…”
Section: Discussionmentioning
confidence: 98%